Oral surgery in patients undergoing head and neck radiotherapy (Research, Society and Development, 2022)
Head and neck cancer (PPC) corresponds to tumors located in the skin, oral cavity, lips, salivary glands, larynx, pharynx, nasal cavity, paranasal sinuses, external acoustic meatus and middle ear. It affects people of both sexes, but with a greater predilection for males and over 40 years of age. The vast majority of patients with HNC are treated with high-dose radiotherapy in this region, commonly administered in daily fractions, over a period of 5 to 7 weeks. This treatment modality generates harmful effects on oral and maxillofacial tissues in patients, such as a marked increase in the risk of dental caries after exposure to radiation. In view of the above, this study aimed to review the literature on oral surgery in patients undergoing head and neck radiotherapy, addressing the oral manifestations resulting from head and neck radiotherapy and oral management strategies for head and neck radiotherapy. For the construction of this article, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. In cases of need for surgical intervention after radiotherapy treatment, extractions should be performed in a minimally invasive way and wait until there is complete healing of the alveolus to start radiotherapy. During irradiation, surgical procedures are not indicated and the dentist's main objective is to prevent or treat oral complications that may arise. Surgical procedures can be performed 6 months after the end of radiotherapy, observing similar results when compared to extractions before radiotherapy.